2006
DOI: 10.1108/13552540610670753
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic finite element analysis of photopolymerization in stereolithography

Abstract: Purpose -This paper aims to introduce the principle of the mask exposure and scanning stereolithography (MESS) and to develop a simulation code to analyze the MESS process. Design/methodology/approach -Photopolymerization is a key reaction in stereolithography. It brings about molecular linkage and releases exothermic temperature. The shrinkage effect is the major cause of prototype deformation, and the shrinkage resulting from scanning and mask exposing is different. It is important to analyze the inaccuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In other methods which have been applied for vat polymerisation processes, light direction is only considered in one direction, where the light diffraction is neglected. Another point that is also important to be noted is that the polymerisation models are mostly related to penetration depth parameters and dimensionless coefficients (Jiang et al, 2006;Sharma, 2008). In these approaches, the behaviour prediction for different material formulations is difficult to be obtained only numerically.…”
Section: Dynamic Finite Element Methodsmentioning
confidence: 99%
“…In other methods which have been applied for vat polymerisation processes, light direction is only considered in one direction, where the light diffraction is neglected. Another point that is also important to be noted is that the polymerisation models are mostly related to penetration depth parameters and dimensionless coefficients (Jiang et al, 2006;Sharma, 2008). In these approaches, the behaviour prediction for different material formulations is difficult to be obtained only numerically.…”
Section: Dynamic Finite Element Methodsmentioning
confidence: 99%
“…Wiedemann et al [46] also performed a numerical analysis on the SLA printing process and revealed a common rule where half the layer thickness doubles the curl. By relating the material modulus and cure shrinkage to the combinations of the averaged energy dose and curing time through several empirical equations, Huang et al [47] developed a dynamic finite element method to simulate the curl distortion of SLA-printed structures and found that short raster scanning produces less distortion than long raster scanning [Figure 2A]. The dynamic finite element method was later adopted by the same authors in another study in order to optimize the scanning parameters [48] .…”
Section: Mechanical Designs For Shape Distortionmentioning
confidence: 99%
“…Mechanical designs for the shape distortion of additive manufactured soft materials. (A) Schematic of the rezoning technique in the dynamic element method simulation of SLA-printed parts [47] . (B) Schematic and experiment result of the deformation of a twolayer resin laminate [40] .…”
Section: Mechanical Designs For Shape Distortionmentioning
confidence: 99%
“…Subsequently, the authors use virtual geometric models to characterize thermal deformation in terms of GD&T characteristics. Jiang et al proposed a simulation model to examine the inaccuracy of the mask exposure scanning stereolithography process [24]. Based on the simulation results, the authors suggested an optimal scan path and exposure time.…”
Section: Physics-based Modeling Approaches (Finite Elementmentioning
confidence: 99%